ANALISIS KESULITAN SISWA KELAS IX DALAM MEMAHAMI MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL (SPLDV) DALAM PEMBELAJARAN DARING - Elis Nurhayati; Puji Nurfauziah; Nelly Fitriani (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This research is a case study research that aims to find out the difficulties of junior high school students in solving SPLDV problems. The subjects in this study were 10 students of class VIII-B MTs Negeri 3 Purwakarta, consisting of 3 students who had low abilities, 4 students who had moderate abilities, and 3 students who had high abilities. The instrument used in this study was in the form of test questions with a description of 6 questions which were arranged based on the cognitive domain of Bloom's taxonomy from the level of questions C3 to C6. The data analysis technique carried out consisted of checking student answers by calculating the percentage of each indicator, determining the type of error in answering the question, and knowing the type of student difficulty. The results showed that students still had difficulties in solving SPLDV problems. The success rate of students in solving SPLDV questions is still relatively low, this can be seen from the number of students who have difficulty solving SPLDV problems, especially on indicators about the ability to apply or use procedures to model and detail the value of the variables asked in a PLDV. The level of difficulty in these indicators is quite high. So that efforts are needed to improve students' ability to understand SPLDV material in online learning.